Mechanical Evaluation Of Femur Geometry And Hip Protectors Using Pendulum-Based System - Iqbal, Ahmad Amir Shafiq Ahmad (Universiti Sains Malaysia, 2019)
Hip fracture due to a sideways fall is a major health problem around the world which causes paralysis and an increased risk of premature death, especially to older people. In this study, a pendulum-based hip impact simulator was developed to mimic a sideways fall. To simulate a direct lateral impact, the external profile of the greater trochanter was used in the previous studies to represent the actual femoral geometry. This study was designed to investigate the potential effects of femoral geometric feature associated with the peak impact force. The result showed that the peak impact force varied only 6% between actual and simplified geometries after normalizing the weight for both femurs. The actual femur geometry has longer time rise to peak force up to 9.1% and total impact time up to 12.12% compared to the impact on simplified femur geometry. Therefore, the study suggested that the simplified femur geometry could be used to represent the actual femur geometry due to the small difference in impact force. The study also investigated the biomechanical comparison of soft (HipSaver) and hard hip protectors. The 3D-printed hard hip protector was designed to specifically complement the hip surface geometry. The results showed that the soft hip protector could increase the time to peak force from 21.72% to 26.67% and total impact time from 23.26% to 29.53% better than the hard hip protector at the highest impact height. With the hip fracture threshold of 5.2kN, the soft hip protector could reduce 10% to 12% peak impact force than the hard-hip protector. In term of safety, the results suggested that the HipSaver could be better to prevent hip fractures than the 3-D printed hip protector.